(3UbhQ GdUMQGA (B:s (3GdMjGI GdjhejI deLGgOj GdhdGjI Gd(B6 (3GdJGQjNjI (B/s - (3OQhGR, GdgGOj GMeOs ((3GdLRGFQ (B:s (3OGQ gheg ddWHGYI h GdfTQ ,s, 2006)
(3GddKhQI(B- (3LHgI GdJMQjQ GdhWfj (B- (3GdeLGgO(B- (3Ghd fhaeHQs
Keywords: (3GdLRGFQs; (3LjT GdJMQjQ GdhWfjs; (3JGQjNs